Taco Bell thanks you for suing them - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
This case describes Taco Bell's 2011 marketing campaign: 'Thank You for Suing Us'. This well-managed campaign was effective enough that it actually led to the withdrawal of a lawsuit against the fast food chain.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). Taco Bell Thanks You for Suing Them. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 218-221). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Taco Bell (Firm); Public relations -- Case studies; Crisis management -- Case studies; Fast food restaurants -- Public relations -- Case studies